2020
DOI: 10.21203/rs.3.rs-100711/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacodynamics of efavirenz 400 mg in treatment-naïve Chinese HIV-infected patients in a prospective cohort study

Abstract: Background: The plasma concentration of patients treated with efavirenz (EFV) 600 mg was found to exceed the upper limit of the proposed therapeutic window in most Chinese HIV-infected individuals; thus, dosage reduction of EFV to 400 mg daily warranted consideration. This study aimed to assess the pharmacodynamics of EFV 400 mg for HIV-1-infected patients in China.Method: Twenty cART-naïve individuals were enrolled in this study. EFV 400 mg combined with tenofovir (TDF) and lamivudine (3TC) as an initial anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In a prospective observational study at Youan Hospital in Beijing, researchers found PLHIV with neuropsychiatric adverse effect at baseline would have severe neuropsychiatric disorders over the 12 months [19,20], however another prospective trial in Peking Union Medical College Hospital found PLHIV diagnosed with depression had no progression in neuropsychiatric co-morbidities [21]. At present, the specific effects of EFV on neuropsychiatric conditions among PLHIV is still controversial, furthermore those studies have short observation periods considering that PLHIV with ART need lifelong medication.…”
Section: Open Accessmentioning
confidence: 99%
“…In a prospective observational study at Youan Hospital in Beijing, researchers found PLHIV with neuropsychiatric adverse effect at baseline would have severe neuropsychiatric disorders over the 12 months [19,20], however another prospective trial in Peking Union Medical College Hospital found PLHIV diagnosed with depression had no progression in neuropsychiatric co-morbidities [21]. At present, the specific effects of EFV on neuropsychiatric conditions among PLHIV is still controversial, furthermore those studies have short observation periods considering that PLHIV with ART need lifelong medication.…”
Section: Open Accessmentioning
confidence: 99%